Being, Belonging and Becoming in Africa: A Postcolonial Rethinking (The Strategic Review for Southern Africa, 2021)
This paper focuses on the nature and signifi cance of belonging and its intersection with Identity and being in the world. Its primary impetus is to address the question of belonging as it arises in postcolonial multi-ethnic, language, religious and racial identities in Africa. Where does ethnic and national Identity intersect and diverge? It remains a highly politicised and contested issue. Narratives on African belongings provide insights into the shape and complexity of the contemporary African debate and illustrate how, in the presentation of belonging as having multiple and competing manifestations, what it is to belong per se is rendered indistinct. This exemplifi es the critical problem where Belonging is concerned. While Belonging is invoked as an issue of crucial existential concern in public discourse and across a broad range of disciplines, there is an apparent and troubling lack of conceptual or linguistic apparatus. The notion can be grasped and critically analysed. Therefore, this paper seeks to explore and redress this problematic situation. Consideration of Belonging also involves Identity and thinking of how these two concepts are articulated together in theory. This latter question is explored by surveying the theoretical and conceptual frameworks from which ‘senses’ of Identity and Belonging are commonly expressed in postcolonial Africa. Belonging qua correct relation represents an entirely new way of understanding, in existential terms, what it is to belong (or not), not only in the postcolonial African context but wherever and whenever the question arises.